2004
DOI: 10.1002/qua.20381
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic exchange interactions in cyano‐bridged MoIII binuclear complexes: Broken‐symmetry and density functional theory calculations

Abstract: Molecular tacnAN, NЈ, NЉ-trimethyl-1,4,7-triazacyclononane) has been calculated using Becke's three-parameter exchange functional and the gradient-corrected functional of Lee, Yang, and Parr (B3LYP), a hybrid density functional theory (DFT), combined with a modified broken symmetry (BS) approach and the post-Hartree-Fock (post-HF) method difference-dedicated configuration interaction (DDCI). We find B3LYP combined with broken-symmetry approach (DFT-BS) give the similar J values to those calculated by DDCI. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The bridges are of the Mo-CN-Mn type and, therefore, the Mn atom with an N 6 coordination sphere is in a high-spin configuration. Models A 1 , A 2 , A 3 , A 4 , and A 5 (the superscript numbers denote the number of exchange interactions) (see Figure 2) were used to investigate the relationship between the nearest-neighbor exchange coupling constants J 12 and the number of exchange interactions. To investigate the relationship between J 12 and the θ angle (we use θ to represent the MoMnMo angle), we obtained three different structures that all include two of the exchange interactions A 2 , A 2Ј , and A 2ЈЈ (see Figure 3).…”
Section: Description Of the Complexes And Modelsmentioning
confidence: 99%
“…The bridges are of the Mo-CN-Mn type and, therefore, the Mn atom with an N 6 coordination sphere is in a high-spin configuration. Models A 1 , A 2 , A 3 , A 4 , and A 5 (the superscript numbers denote the number of exchange interactions) (see Figure 2) were used to investigate the relationship between the nearest-neighbor exchange coupling constants J 12 and the number of exchange interactions. To investigate the relationship between J 12 and the θ angle (we use θ to represent the MoMnMo angle), we obtained three different structures that all include two of the exchange interactions A 2 , A 2Ј , and A 2ЈЈ (see Figure 3).…”
Section: Description Of the Complexes And Modelsmentioning
confidence: 99%
“…We have also used Equation (15) to evaluate binuclear Mo III complexes and also found that the J values are almost linearly related to -(ρ HS 2 -ρ BS 2 ). [55] The spin populations were obtained by PW91 calculations on the basis of a Mulliken population analysis [53] using the first approach. Due to the symmetry of the structures, we only give the results for one of the Cu II ions (Table 3).…”
Section: Qualitative Analysis Of the Exchange Interactionmentioning
confidence: 99%
“…In a recent work, Desplanches et al 4 succeeded in calculating the exchange coupling constants in metal complexes of the second transition series, using density functional theory (DFT) combined with Noodleman's broken‐symmetry (BS) approach 5–7. We 8 also selected two cyano‐bridged Mo III binuclear complexes [Mo 2 (CN) 11 ] 5− 1 and [(Me 3 tacn) 2 Mo 2 (CN) 5 ] + (Me 3 tacn = N , N ′, N ″‐trimethyl‐triaz‐acyclononane) 2 to analyze the magneto‐structural correlations and the mechanisms of the magnetic coupling interactions through the spin‐density maps, using DFT‐BS. In the above theoretical work, Desplanches et al 4 and Zhang et al 8 only investigated the homo‐binuclear second transition metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…We 8 also selected two cyano‐bridged Mo III binuclear complexes [Mo 2 (CN) 11 ] 5− 1 and [(Me 3 tacn) 2 Mo 2 (CN) 5 ] + (Me 3 tacn = N , N ′, N ″‐trimethyl‐triaz‐acyclononane) 2 to analyze the magneto‐structural correlations and the mechanisms of the magnetic coupling interactions through the spin‐density maps, using DFT‐BS. In the above theoretical work, Desplanches et al 4 and Zhang et al 8 only investigated the homo‐binuclear second transition metal complexes. However, we selected four cyano‐bridged hetero‐trinuclear and hetero‐polynuclear complexes to investigate the magnetic properties extending the research of magnetic coupling mechanism of 4 d systems.…”
Section: Introductionmentioning
confidence: 99%